2015
DOI: 10.1111/1467-9477.12052
|View full text |Cite
|
Sign up to set email alerts
|

Political Trust, Individual‐level Characteristics and Institutional Performance: Evidence from Finland, 2004–13

Abstract: Several scholars agree that low political trust has fundamental negative implications for society at large. This study tests the power of institutional performance theory in explaining the differences between individuals in political trust (cross-sectional) and fluctuations of political trust over time (longitudinal). Indeed, the dominant scholarly debate has concerned whether political trust is stable and dependent of endogenous factors such as political socialization and social trust, or whether it is exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 67 publications
(111 reference statements)
0
26
0
Order By: Relevance
“…As for services/protection, we go beyond a small number of oft-used European Social Survey items (e.g. Kestilä-Kekkonen and Söderlund 2016;Kumlin 2007;Lühiste 2014) and consider a wider range of perceived welfare state performance aspects.…”
Section: Introductionmentioning
confidence: 99%
“…As for services/protection, we go beyond a small number of oft-used European Social Survey items (e.g. Kestilä-Kekkonen and Söderlund 2016;Kumlin 2007;Lühiste 2014) and consider a wider range of perceived welfare state performance aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent literature suggests that citizens also consider welfare state-related policy outputs, outcomes and performance evaluations (e.g. Haugsgjerd, 2018;Kestilä-Kekkonen & Söderlund, 2016;Lühiste, 2014). A review chapter (Kumlin and Haugsgjerd, 2017) illustrates how macro-variables related to inequality and welfare generosity, as well as individual assessments of services, affect political trust.…”
Section: Lessons From Research On Performance and Political Trustmentioning
confidence: 99%
“…Finally, the article provides a methodological contribution to the study of political trust among emigrants. The emigrants from wealthy welfare states, such as Finland, can be assumed on average to be more educated and have higher income than resident citizens (see e.g., Kepsu and Henriksson, 2019). Research has shown these socio-economic factors to be related to higher social and political trust (Inglehart, 1999), although the relation can be complex, as for instance between education and political trust (Norris, 2011).…”
Section: Ols and Psmmentioning
confidence: 99%